Effects of Coach’s Verbal Encouragement During Small-Sided Volleyball Games on Specific Physical Fitness and Technical-Tactical Behavior of Youth Athletes - Taufiq Hidayat; Irma Febriyanti; Advendi Kristiyandaru; Suroto; Hari Wisnu; Ahmet Kurtoğlu; Amayra Tannoubi; Joseph Lobo; Baglan Yermakhanov; Jarosław Muracki; Edi Setiawan (Physical Activity and Health)
Purpose: This study aims to investigate the impact of coach’s verbal encouragement small-sided volleyball games (CVESSVG) towards specific physical performance, and technical-tactical behavior among youth athletes. Methods: There were forty youth male volleyball athletes involved in this study, which were allocated in CVESSVG (n = 20), and small-sided game-non coach’s verbal encouragement (SSG-non CVE) (n = 20). Physical performance including agility t-test (ATT), 10-m sprint test (10-mST), countermovement jump test (CMJT), medicine ball throw test (MBTT), multistage 20-meter shuttle run test (M20-MSRT), and technical-tactical behavior (serve, reception, sets, attack, defense) were measured in pre-test and post-test. Results: The results of the 2-Way ANOVA showed that there were differences in physical performance based on effect factors (all, p < 0.05), interaction factors (p < 0.05), except MBTT (p > 0.05), group factors (p < 0.05), except MBTT (p > 0.05). In addition, there were differences in technical-tactical behavioral factors based on time effects (all, p < 0.05), interaction factors (p < 0.05), except service (p > 0.05), and group factors (all, p < 0.05). Conclusions: It can be concluded that CVESSVG was more effective than SSG-non CVE in order to improve physical performance variables, and technical-tactical behavior among youth athletes.